Face-to-face versus distance learning: perception of students in a health school - Poças, Ilda Maria (2023)
Introduction – Facing the pandemic situation of COVID-19, which occurred in 2020, higher education institutions needed to adapt, transitioning from face-to-face teaching to distance emergency teaching, and therefore, in an online format. Objectives – To analyze the perception of students from a higher school of health, facing the teaching transition, focusing mainly on the preference and satisfaction for the type of teaching, adaptation difficulties, motivation, changes in emotional states, academic performance, acquired skills, and visual changes. Methods – Descriptive research was conducted by applying an online questionnaire to the sample under study. The data were analyzed using SPSS. Results – The results obtained indicated that, of the 517 answers, 40.4% (n=207) stated that they preferred face-to-face teaching, 43.9% (n=207) felt that they had greater difficulty in adapting to practical teaching, and 29.3% (n=143) were more satisfied with theoretical classes as opposed to practical classes. Conclusion – In the sample under study, there is dissatisfaction with distance learning, particularly in practical classes, as it was the type of learning that presented the most difficulties in adaptation, with an intensification of negative emotional states, a decrease in motivation, and a decrease in the student’s academic skills, as well as a preference for face-to-face learning.